Characteristics of Tenders As A Pre-Contract Stage for the Procurement of Goods and Services - Hasran Hasran; Addy Indrasakti; Agung Salim Wicaksono (Jurnal Indonesia Sosial Teknologi, 2024)
Tendering in procuring goods and services is a crucial early stage in forming a fair procurement contract. This study aims to analyse the characteristics of tenders as a pre-contract stage of public procurement of goods and services. This research uses a qualitative research method with a descriptive approach. A literature study carried out the data collection technique in this research. The data that has been collected is then analysed in three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the characteristics of tenders as a pre-contract stage of government procurement of goods and services include competitive, fair, transparent, efficient, and effective. These tender characteristics are essential to consider in procuring government goods and services to produce quality goods and services providers who can carry out work correctly and on time